Morphological and Molecular Evaluation of a Gel Based on Hyaluronic Acid and Spermidine for Oral Regenerative Purposes - Dolaji Henin; Elena Canciani; Daniela Carmagnola; Stefano Ferrero; Gaia Pellegrini; Mariachiara Perrotta; Riccardo Sirello; Claudia Dellavia; Nicoletta Gagliano (Cells)
Background: Oral wound healing is a complex process influenced by extracellular matrix (ECM) remodeling and cellular migration. Hyaluronic acid (HA) and spermidine (SP) have shown regenerative potential, but their combined effects on oral tissues remain unexplored. This study aimed to characterize the effect of a gel composed of a mixture of HA and SP on the epithelial and connective compartments of oral tissue separately, evaluating (i) collagen turnover and cell migration on primary human gingival fibroblasts (HGFs) and (ii) epithelial integrity and cell proliferation on gingival organotypic cultures (OCs). Methods: HGFs were cultured, treated with HA-SP gel (1:0.5 HA-SP ratio) and evaluated for collagen types I and III (COL-I, COL-III), matrix metalloproteinase (MMP-1) protein and tissue inhibitor of MMP-1 (TIMP-1) levels secreted by the cells upon gel treatment, compared to CT. HGFs were also analyzed through a wound healing assay. Gingival samples were obtained to set OCs and were treated with different HA-SP formulations (HA 0.2%; 1:0.5 HA-SP ratio; 1:5 HA-SP ratio) to evaluate the beneficial addition of SP to HA for epithelial tissue. OC samples were formalin-fixed and paraffin-embedded and were stained with hematoxylin and eosin and immunostained for Ki-67 analysis. Results: In HGFs, the gel induced increased COL-III gene expression relative to that of COL-I after 48 h and stimulated cell migration, in turn favoring connective tissue remodeling and repair. In OCs, the gel preserved epithelial integrity up to 48 h, with the best effects observed with the 1:0.5 HA-SP ratio. After 72 h, epithelial detachment was more evident in HA formulations, suggesting that SP contributes to epithelial integrity. Conclusions: The HA-SP gel may support oral tissue healing by modulating ECM remodeling and maintaining epithelial integrity. The gel containing HA and SP at the 1:0.5 ratio may provide a promising solution for enhancing wound healing.